Television and empire: on the absence of emissions of the portuguese television stationin the overseas provinces - Cádima, Francisco Rui (Media & Jornalismo, 2016)
In this text we will try to understand some of the fundamental reasons for the fact that television never reached the Portuguese colonies, either during the government of Salazar or even with Marcello Caetano, although he was the promoter of television in Portugal. The analysis of national and international political context and the confrontation with the South African own experience, more determined in its “cathodic iconoclasm”, some of the conclusions we draw lead us to a question that the very political and media experience of apartheid seems to suggest an answer. And that has to do with the possible impacts of another television propaganda strategy in the colonial context. What diverse consequences could that have had? Let the reader be here him or herself to withdraw its conclusions.